Tables showing numbers of officers and men, casualties, prisoners, arms and enemy strength, in each Irish Republican Army 1st Southern Division Brigade area after the Truce - Irish Republican Army. Southern Command, 1st; Deasy, Liam, 1896-1974 (1921)
Covers Brigade areas Cork Nos. 3-5, Kerry Nos. 1-3 and Waterford. Enemy strength during War broken down by Royal Irish Constabulary, Auxiliaries, military and marines. With summary of returns for all brigade areas by Liam Deasy, [Commandant, Cork No. 3 Brigade].
Keywords: Irish Republican Army. -- Southern Command, 1st; Royal Irish Constabulary; Ireland -- History -- War of Independence, 1919-1921; Ireland -- History -- 1910-1921